An investigation of the influence of skin colour on the perception of femininity, masculinity and likeable - Wang, Mengmeng; Zhang, Jingzhe; Chen, Jiapei; Zhang, Liyi (Frontiers in Psychology, 2022)
Skin colour, a key factor related to facial impressions, is widely used by CG character designers to build characters with different storylines. The previous research provided essential suggestions for creating an attractive facial image. However, the beauty concept is changed in the latest decade. The suggestions of the prior research are insufficient for building the characters to resonate with the current public, especially the young people. The present study investigates the influence of skin colour (whiteness and hue angle) on the femininity, masculinity and likableness perception of Chinese female and male images. A psychophysical experiment was carried out to investigate these relationships. The results reveal that whiteness significantly impacted the feminine-masculine perception of the Chinese male image and the likableness perception of the Chinese female and male image. The hue angle only significantly influenced the likability perception of the Chinese female image.